PENGARUH PERMAINAN KOTAK POS TERHADAP KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI PADA ANAK USIA 5-6 TAHUN DI TK AL-ITTIHAD KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Wita Sari; Daviq Chairilsyah; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the effect of post box games on the ability to recognize geometric shapes in children aged 5-6 years in TK Al-Ittihad, District of Rumbai Pesisir, Pekanbaru City. The population in this study were children aged 5-6 years in TK Al-Ittihad, District of Rumbai Pesisir, Pekanbaru City, amounting to 20 people, the sample of this study was 20 people. The method used is the One Group Pre-test-Post-test design to see the influence of the variable postbox play on the ability to recognize geometric shapes. Data collection techniques used are observation. Data analysis techniques using linearity test, homogeneity test, normality test, correlation test and hypothesis testing with SPSS for Windows Ver. 17. Based on the results of the hypothesis test obtained there is a positive and significant influence between the postbox game on the ability to recognize geometric shapes in children aged 5-6 years in TK Al-Ittihad, Rumbai District, coastal city of Pekanbaru. This can be seen from the hypothesis value of t = 35,396 and the significance level of 0.00 <0.05. The effect of post box play on the ability to recognize geometric shapes in children is included in the medium category with the value of the centralized gain generated at 57.66%, meaning that the postbox game has an effect of 57.66% on the ability to recognize geometric shapes.Keywords: Geometry Form, Post box Game